2018
DOI: 10.1111/jfb.13843
|View full text |Cite
|
Sign up to set email alerts
|

MHC class IIA polymorphisms and their association with resistance–susceptibility to Streptococcus agalactiae in Nile tilapia, Oreochromis niloticus

Abstract: The association between major histocompatibility complex (MHC) class IIA polymorphisms and the severity of infection by Streptococcus agalactiae was investigated using 40 susceptible and 40 resistant individuals of Nile tilapia Oreochromis niloticus. Twenty‐five alleles were identified from 80 individuals, which belong to 22 major allele types. High polymorphism of mhcIIa gene and at least two loci were discovered in O. niloticus. In peptide‐binding region (PBR) and non‐PBR, the ratio of nonsynonymous substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(94 reference statements)
1
0
0
Order By: Relevance
“…Tests of codon substitution models also revealed that the codon sites that were under selection closely matched the inferred antigen-binding sites from the human HLA molecule. Our results showing that selection acts on functional codons within the MHC are consistent with previous studies in ungulates and other vertebrates, namely white-tailed deer [ 69 , 70 ], musk deer [ 43 ], red deer [ 71 , 72 ], moose [ 58 ], cattle and other ruminants [ 21 , 73 ], Nile tilapia [ 74 ] and prairie chickens [ 75 ].…”
Section: Discussionsupporting
confidence: 91%
“…Tests of codon substitution models also revealed that the codon sites that were under selection closely matched the inferred antigen-binding sites from the human HLA molecule. Our results showing that selection acts on functional codons within the MHC are consistent with previous studies in ungulates and other vertebrates, namely white-tailed deer [ 69 , 70 ], musk deer [ 43 ], red deer [ 71 , 72 ], moose [ 58 ], cattle and other ruminants [ 21 , 73 ], Nile tilapia [ 74 ] and prairie chickens [ 75 ].…”
Section: Discussionsupporting
confidence: 91%